VALUE CO-CREATION AND SOCIAL NETWORK ANALYSIS ON A NETWORK ENGAGEMENT PLATFORM - DONATO,HELLEN CLAUDIA (2017)
ABSTRACT Purpose: The study identifies value co-creation resulting from the influence of relationships, using the DART model, on an engagement platform in a specific network of companies in the Great ABC Region, which does not allow competition, that is, only one company by activity sector and contemplates different business segments with the objective of mutual benefit. Originality/value: A gap in theory regarding value co-creation based on the relationship in the cooperation network with different segments, in which clients are independent organizations. Design/methodology/approach: The research is a descriptive case study of a network named co-creative. The data were obtained from the centrality and density metrics, from the social networks analysis (SNA), besides the information obtained from the document analysis, the non-participant observation technique and interviews with the network components. Findings: There were 12 results of co-creation of values, of which five were completed: development of Biblical APP, personal marketing for digital media, opening of a company in search of financial resources, digital marketing with animation for corporate videos and Coaching speciali zed in self-esteem for men and women. These results of co-creations were analyzed based on the relationships of the engagement platform provided by the network. Another six co-creations are underway and one under study.